Management of radioactive wastes issues for local authorities : proceedings of the UK Nuclear Free Local Authorities Annual Conference 1997, held at Town House, Kirkcaldy, Fife, on 23 October 1997 - Barker, F. (Thomas Telford, 1998)
Pinpoints the key issues of management of radioactive wastes. The contributors have not only put forward ideas with the aim of contributing to the fundamental policy review that is needed in the UK, but also added their views to the international debate on this important topic. It aims to propose recommendations for policy changes.